Dose adjusted EPOCH-R is superior to RCHOP in frontline treatment of mediastinal large B cell lymphoma - Mohammad Ma'koseh; Abeer Yaseen; Nebras Abu Abed; Omar Shahin; Alaa Abufara; Khalid Halahleh; Mohammad Al-Rwashdeh; Zaid Abdel Rahman; Ro’a Muqbel; Heba Farfoura; Akram Al-Ibraheem; Kamal Al-rabi; et al. (Hematology)
Introduction Primary Mediastinal Large B Cell Lymphoma (PMLBCL) is a rare but aggressive B-cell lymphoma. This study compares the outcomes and toxicities of DA-EPOCH-R (Dose-adjusted etoposide, prednisolone, vincristine, cyclophosphamide, and doxorubicin in combination with rituximab) and RCHOP-21 (rituximab, cyclophosphamide, doxorubicin, and vincristine, every 21 days) in the treatment of newly diagnosed PMLBCL.Methods We retrospectively reviewed the medical records of adults (>18 years) diagnosed with PMLBCL and treated at our center from 2010 to 2023. Baseline characteristics were compared using chi-square and Mann Whitney U-tests. Survival outcomes were analysed using Kaplan Meier and log-rank tests.Results Eighty-seven patients were included, with a median age of 30 years (range: 18–55), 48 patients (55.2%) received RCHOP-21, and 39 patients (44.8%) received DA-EPOCH-R. Radiotherapy was more frequent in the RCHOP-21 group (66.6% vs 15%, p < 0.001). DA-EPOCH-R achieved a higher complete metabolic response (CMR) (92% vs 69%, p = 0.007). After a median follow-up of 47.4 months, patients treated with DA-EPOCH-R had superior overall survival (OS) and progression free survival (PFS); 3-year OS rates were 94.4% vs 69.8% (p = 0.01) and the 3-year PFS rates were 86.7% vs 62.2% (p = 0.016), particularly in patients with aa-IPI >1. Post-chemotherapy delta SUV max <0.75, and <0.7 correlated with relapse and mortality, respectively. Grade III-IV anemia and non-hematological toxicities were more frequent in the DA-EPOCH-R, but no therapy-related deaths occurred.Conclusions DA-EPOCH-R improves CMR, PFS, and OS compared to R-CHOP-21 with radiotherapy in PMLBCL, particularly in high-risk patients. Longer follow-up is needed to assess long-term toxicities.